Modelling oligomerization of p53 family. - Lee, Yin Yeng. (2010)
Oligomerization is essential for the biological functions of p53 family members (p53, p63 and p73) in cell-cycle arrest and development, and the oligomerization domain of these proteins is found to be the main tetramerization site. Recent studies have reported that the p53 family members can interact with each other, forming heterotetramers. Moreover, p73tet without the H2-helix is reported to form higher level oligomers in vitro. The main focus for this study is to understand the oligomerization of p53 family members at the oligomerization domain. This work is carried out using computational modelling to analyze the binding energetic conformity with the respective models. This information is then further applied to the models built by MODELLER, to find out how feasible the formation of heterotetramer and higher level oligomers are. Results show that p53tet/p63tet and p53tet/p73tet are more likely to form heterotetramers with heterodimers; whereas p63tet/p73tet is more likely to form heterotetramers with homodimers. p73 without its terminal helix forms hexamers which p53 cannot form due to high electrostatic repulsion.